PEMBUATAN VIRTUAL REALITY PARIWISATA KERETA API UAP JALADARA DI SURAKARTA MENGGUNAKAN UNITY 3D GAME BERBASIS ANDROID - Firma Sahrul Bahtiar; Imam Putra Setyawan (IJAI (Indonesian Journal of Applied Informatics), 2016)
The use of virtual reality technology can be applied to introduce tourism in the city of Surakarta. One of the attractions is a mainstay of Surakarta is Kluhuk Jaladara Scenic railroad. This tour allows you to enjoy the city of Surakarta with shades of ancient times. Unfortunately, to hire a buggy is quite expensive because of fuel use genuine teak. So the need for these applications to attract tourists that are willing to try the thrill of boarding the train Jaladara after trying railroad Kluthuk Jaladara Virtual application. The results of this research is the application of Virtual railroad Kluthuk Jaladara run on android device with a sensor gyroscope 3D Virtual Reality: Virtual tourist steam train Surakarta expected to create a visual picture of the travel in Surakarta, so it can serve as a medium for the introduction of travel and also as a means of information interactive.